NETWORK DEVICE MONITORING SYSTEM BASED ON GEOGRAPHIC INFORMATION SYSTEM DAN SIMPLE NETWORK MANAGEMENT PROTOCOL - Hizriadi, Ainul; Shiddiq, Radea; Jaya, Ivan; Prayudani, Santi (Universitas Medan Area, 2020)
Network infrastructure monitoring is an important part of an institute to maintain the stability of computer network devices. One of the functions of computer network monitoring is to find out the data traffic generated in network application. Simple Network Management Protocol is one of protocols for monitoring the data traffic in network device. However, network device administrators still have problems when they want to monitor their network infrastructure, such as device location and data traffic information of network device that is only temporarily stored in the monitoring system, and physical location of network device is not contained in the monitoring system. In order to make it easier for them how to monitor network devices, the Researcher intends to combine Geographic Information Systems (GIS) and SNMP into a web-based monitoring application. Geographic Information System application can display the physical location of network devices, whilethe SNMP application using for monitoring the data traffic in network device,finding out the data traffic that can be generated in real time, and displaying data traffic of network device that has been monitored in to graphical form based on the time and network device used.